1993
DOI: 10.2527/1993.713730x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of orally administered β-carotene by blood plasma, leukocytes, and lipoproteins in calves1

Abstract: The uptake of beta-carotene by blood cells, plasma, and lipoproteins was studied in bull calves that were orally administered a single (Exp. 1; n = 18 Angus calves) or multiple (Exp. 2; n = 16 Holstein calves) doses of beta-carotene. Administration of beta-carotene increased plasma beta-carotene and the amount of beta-carotene associated with each lipoprotein fraction. Before beta-carotene treatment, the total amount of beta-carotene associated with the high-density lipoprotein (HDL) was three- to fourfold hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Our results and those from studies in humans [37], in which β-carotene was given as a supplement, indicate that an increase in plasma of β-carotene concentrations has minimal impact on plasma retinol concentrations. Chew et al [10] also reported that oral administration of β-carotene to calves fed a diet containing normal concentrations of vitamin A does not affect plasma retinol concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and those from studies in humans [37], in which β-carotene was given as a supplement, indicate that an increase in plasma of β-carotene concentrations has minimal impact on plasma retinol concentrations. Chew et al [10] also reported that oral administration of β-carotene to calves fed a diet containing normal concentrations of vitamin A does not affect plasma retinol concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In preruminant calves, oral supplementation with BC results in a plasma BC response [80, 83, 142, 143] as well as increases in tissue BC concentration [80, 143]. Hoppe et al [144] found a dose-response relationship between dietary BC and plasma, liver, and perirenal BC and hepatic VA concentrations, providing evidence that calves both absorb BC intact and convert it to VA. Kon et al [145] found that calves converted orally administered BC to VA in blood and liver, while an intravenous injection of BC did not result in increased VA.…”
Section: Species Differences In β-Carotene Metabolismmentioning
confidence: 99%
“…Plasma BC also accumulated in plasma, lymphocytes, and neutrophils when dogs were dosed for up to 30 days with BC [175]. However, the plasma response to the BC dose was much lower in dogs compared to similar single dose studies in cats [177], ferrets [178], and calves [142, 143]. …”
Section: Species Differences In β-Carotene Metabolismmentioning
confidence: 99%
“…The cholesterol that arrives at the ovary via the blood stream is transported by either high-density lipoprotein (HDL) or low-density lipoprotein (LDL), depending on the animal species. LDL cholesterol accounts for the majority of blood cholesterol in pigs (12), whereas HDL cholesterol predominates in goats (13) and bovines (14).…”
Section: Introductionmentioning
confidence: 99%